Bonjour, butterfly - O'Connor, Jane (O'Connor, Jane. Fancy Nancy., 2008)
Nancy is furious when she cannot go to her friend Bree's butterfly-themed birthday party, but her family's outing might just be extraordinary enough to make her feel better. Includes facts about butterflies.